Improved Spring-Back Compensation Strategy through Location Optimized Part Position in the Dies. (November 2019) - Birkert, A; Hartmann, B; Lepple, F; Straub, M; Zimmermann, P
Abstract: Further increasing requirements to the quality of car body components represent a huge challenge for the process planner. As the elastic energy is changing in each stamping operation, it is quite challenging to decide how to compensate which stamping operation. The belonging process definition is known as the compensation strategy. A key prerequisite of an appropriate compensation strategy is a proper location of the part in all stamping operations along the process chain. Proper means that the distance of the part to the die must be minimal to prevent any undefined shift of the part in the die and thus unwanted deformations when closing the dies. Both shifting and deformations would cause dimensional deviations and surface defects. Today different strategies are applied to meet these requirements at least approximately. Strategies, which are published in different papers yet, can only provide suboptimal results. Here a new compensation strategy is being presented, which fulfils the requirement to a proper part location not only in the trimming dies, which corresponds to the so-called Drawshell Strategy, but also in the restriking dies. An important advantage of the respective strategy is that it generally can be applied on all multistage car body stamping operations.